Spatially resolved gene regulatory and disease-related vulnerability map of the adult Macaque cortex - Ying Lei; Mengnan Cheng; Zihao Li; Zhenkun Zhuang; Liang Wu; Yunong sun; Lei Han; Zhihao Huang; Yuzhou Wang; Zifei Wang; Liqin Xu; Yue Yuan; et al. (Nature Communications, 2022)
Cell type epigenetic and topographic information of primate brain is lacking. Here, authors identified transcriptional regulatory network, gradient expression pattern and disease vulnerability at cell type level in PFC, M1 and V1 of monkey brain by snRNAseq, snATAC-seq and Stereo-seq.